A study of risk factors for breast cancer in Al-Anbar province: a case- control study (Journal of Ideas in Health, 2023)
Background: Globally, breast cancer is a widespread malignancy among women, ranking as the second leading cause of female mortality. This study investigates risk factors for breast cancer in AL-Anbar province, Iraq, emphasizing their significance in disease development. Methods: An investigation was carried out at Al-Anbar Cancer Center in Al-Anbar province, Iraq, employing a case-control design. The study comprised 60 confirmed breast cancer cases and 120 controls without breast issues. Data was collected through direct interviews using a semi-structured questionnaire, and subsequent analyses included descriptive, bivariate, and multivariate approaches.Results: About 48.0% aged 41-49, and 25% aged 50-59. Case and control groups were matched in age, but varied in marital, education, occupation, menopausal status. Women with benign breast diseases have a 1.7 times higher breast cancer risk (OR=1.7, CI=0.063-4.53). Positive family history triples the risk (OR=3, CI=1.21-7.80, P=0.002), and the sedentary lifestyle exhibits 5 times higher risk of breast cancer (OR=5.67, CI=2.89-4.13, P < 0.001). Menstrual age, parity, and reproductive factors influence breast cancer risk. Menarche at ≤12 years triples the risk (OR=3.05, CI=1.82-5.05, P